Defective Cell Cycle Checkpoints as Targets for Anti-Cancer Therapies - Gabrielli, Brian; Brooks, Kelly; Pavey, Sandra (Frontiers in Pharmacology, 2012)
Conventional chemotherapeutics target the proliferating fraction of cells, which will include the tumour cells, but are also toxic to actively proliferating normal tissues. Cellular stresses, such as those imposed by chemotherapeutic drugs, induce cell cycle checkpoint arrest, and recent approaches targeting these checkpoints are being explored to increase the efficacy and selectivity of treatment. Loss of a checkpoint may also make cancer cells more reliant on other mechanisms to compensate for the loss of the checkpoint function which may be targeted using synthetic lethal approaches. Here we will discuss the utility of targeting checkpoint defects and approaches that are currently being explored as novel anti-cancer therapies.